Pembelajaran E-Learning Berbasis Web Bagi Pengajar untuk Mendukung Kegiatan Perkuliahan di Politeknik Negeri Padang - Maimuzar - -; Nasrul - - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2017)
We-based e-Learning System can be used to support lecture’s activity. Lecturer as a teacher need a servise of the Sistim which suitable for their activities. Lecturer’s activities consist of delivering materials, discussion and interaction with their students. Because of that the aplication design is needed to support the activities of lectures. Designing the web based e-Learning System is intended to give a service on the lecture. Lecture can do their teaching activities, delivering the materials and administering it using this e-Learning aplication. From the student side, they have to receive the materials easily from anywhere at anytime. This research have an objective to design a web based e_learning System which give an adequate service supporting the lecturer’s activities. Lecture can use this aplication ti deliver their materials, communicating and interacting with their student, observing the progress of students and give result of learning evaluation from the web. The design and implementation of this e-learning application is based on the requirement of the users. The users consist of lecturer, student, quest, and administrator. The process of aplication design is built within Sistimatical stages. After finishing the design process, the aplication is implemented on the real Sistim. Doing the design testing and functional is to test if the aplication can go well together with design and funtionality.e-Learnign aplication that has been built is designed based on lecturer’s need when doing their lecture’s activities. This e-Learning aplication can be used as contribution for building new aplication or5 improving others that has already exist.